Pendekatan Intervensi Pengembangan Organisasi Menurut Tenaga Administrasi di SDN 01 Bungo Pasang, Kota Padang - Muhammad Adzikra Irsy (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
This study aims to analyze the application of intervention approaches in organizational development at SDN 01 Bungo Pasang. Using qualitative methods through observation, interviews, and documentation, this study identifies the types of interventions applied as well as the supporting and inhibiting factors. The results show that the school understands intervention as a planned action to improve organizational conditions so that educational goals can be achieved more effectively. The school implements three main types of interventions: academic (remedial programs and literacy guidance), administrative (e-report card system), and cultural (5S habit formation). The implementation of interventions is carried out systematically with a collective approach based on deliberation and a culture of mutual cooperation. Despite facing obstacles, particularly in adapting to digital technology and resistance to change, the commitment and cooperation of the entire school community is key to the success of organizational development. This study provides practical contributions to improving the managerial capacity of elementary schools in Indonesia.